Molecular Characterization of a Novel Enamovirus Infecting Raspberry - Koloniuk, Igor; Fránová, Jana; Přibylová, Jaroslava; Sarkisova, Tatiana; Špak, Josef; Tan, Jiunn Luh; Zemek, Rostislav; Čmejla, Radek; Rejlová, Martina; Valentová, Lucie; Sedlák, Jiří; Holub, Jan; et al. (Viruses, 2023)
Raspberry plants, valued for their fruits, are vulnerable to a range of viruses that adversely affect their yield and quality. Utilizing high-throughput sequencing (HTS), we identified a novel virus, tentatively named raspberry enamovirus 1 (RaEV1), in three distinct raspberry plants. This study provides a comprehensive characterization of RaEV1, focusing on its genomic structure, phylogeny, and possible transmission routes. Analysis of nearly complete genomes from 14 RaEV1 isolates highlighted regions of variance, particularly marked by indel events. The evidence from phylogenetic and sequence analyses supports the classification of RaEV1 as a distinct species within the Enamovirus genus. Among the 289 plant and 168 invertebrate samples analyzed, RaEV1 was detected in 10.4% and 0.4%, respectively. Most detections occurred in plants that were also infected with other common raspberry viruses. The virus was present in both commercial and wild raspberries, indicating the potential of wild plants to act as viral reservoirs. Experiments involving aphids as potential vectors demonstrated their ability to acquire RaEV1 but not to successfully transmit it to plants.
Keywords: Aphids; Animals; Rubus; Viruses; mšice; Phylogeny; Luteoviridae; viry; nemoci rostlin; zvířata; fylogeneze; HTS; raspberry; Plant Diseases; virus; aphid transmission